Unmet Need of Family Planning Among Rural Women in Bangladesh - Ferdousi, SK; Jabbar, MA; Hoque, SR; Karim, SR; Mahmood, AR; Ara, R; Khan, NR (Journal of Dhaka Medical College, 2010)
Objective: This study aims to find out the unmet need of family planning among the rural women. To explore the obstacles to use family planning methods and to estimate the prevalence of contraceptive use. Study design: Cross-sectional type of descriptive study. Settings: The study was conducted at Sreepur upazila under Gazipur district. Subjects: All the married women of reproductive age, residing in a selected village of Sreepur upazila, were selected as the study subject. Results: The study revealed that unmet need was (22.4%). Most of the respondents (72.1%) were using contraceptive methods. Among those who used contraceptives, OCP was the most commonly used method (61.7%). About 28% were not using any method. The main reason was fear of side effects (46.1%). Conclusion: The study concluded that a nationwide contraceptive prevalence study may be carried out to explore the problem in detail. Key words: Unmet need; family planning; contraceptive prevalence rate. DOI: 10.3329/jdmc.v19i1.6244 J Dhaka Med Coll. 2010; 19(1) : 11-15.